Exploring Determinants of Surrogate Decision-Maker Confidence: An Example From the ICU. (October 2014) - Bolcic-Jankovic, Dragana; Clarridge, Brian R.; LeBlanc, Jessica L.; Mahmood, Rumel S.; Roman, Anthony M.; Freeman, Bradley D.
This article is an exploratory data analysis of the determinants of confidence in a surrogate decision maker who has been asked to permit an intensive care unit (ICU) patient's participation in genetic research. We pursue the difference between surrogates' and patients' confidence that the surrogate can accurately represent the patient's wishes. The article also explores whether greater confidence leads to greater agreement between patients and surrogates. Our data come from a survey conducted in three hospital ICUs. We interviewed 445 surrogates and 214 patients. The only thing that influences patients' confidence in their surrogate's decision is whether they had prior discussions with him or her; however, there are more influences operating on the surrogate's self-confidence. More confident surrogates are more likely to match their patients' wishes. Patients are more likely to agree to research participation than their surrogates would allow. The surrogates whose response did not match as closely were less trusting of the hospital staff, were less likely to allow patient participation if there were no direct benefits to the patient, had given less thought about the way genetic research is conducted, and were much less likely to have a person in their life who they would trust to make decisions for them if they were incapacitated.